Attitudes towards the development of wind farms in Australia - Bond, Sandy (Environmental Health Australia, 2008)
The Australian government is supporting the development of renewable energy technology, such as wind power, in its efforts to reduce greenhouse gases in line with the Kyoto agreement. While wind technology offers many advantages, property owners have voiced opposition to the siting of wind farms due to concerns over changes in neighbourhood aesthetics, noise, loss of bird life, and loss in property values. Such opposition can result in planning permission being declined and a restriction in the ability to meet Kyoto targets. This paper outlines the results of research carried out in Western Australia in 2008 to investigate the attitudes of residents towards the development of a wind farm. The results indicate that the majority of the respondents think of a wind farm in positive terms. The proximity to the wind farm is an important aspect that could determine attitudes with many respondents reporting that they would not want to live “near” a wind farm, usually stated as between 1-5km. Over a third (38%) of the respondents would pay 1-9% less for their property due to the presence of a wind farm nearby. These results will be of interest to power companies in helping to plan the siting of wind farms.